Perceptions of adolescent pregnancy in the rural context and the Colombian armed conflict: a qualitative approach based on social determination of health - Herlan Palacios-Perdomo; Naydú Acosta-Ramírez (BMC, 2021)
Abstract Background Adolescent pregnancy in rural areas is a persistent health problem that has still not properly been understood. Studies with qualitative perspectives that address this phenomenon as a complex social process, which involves the recognition of the voices of the actors involved and the analysis of the specific context in which it takes place, are limited. Objective This research explored the perceptions of young people and other social actors (municipalities of Palmira and El Cerrito in Colombia) of the social forces and dimensions of the social determination of adolescent pregnancy in the Amaime river basin. These geographic areas have been scenes of armed violence with various groups in combat within the context of a long-standing political conflict in Colombia. After the 2016 Havana agreements were signed, peacebuilding has been underway in its territories. Methods A qualitative study that implemented focus groups and semi-structured interviews was conducted. The theoretical approach of social determination of health proposed by Breilh was used to study the social process entailed in adolescent pregnancy. Perceptions about social conditions, specific ways of life, and lifestyles were addressed. Galtung and Fischer's theoretical approach on violence and peacebuilding was also incorporated to enrich the understanding of the Colombian context. The analysis was conducted with approaches from phenomenology. Results Living conditions with strong social stigma and demand for social, political, and cultural opportunities were found. Regarding ways of life, little communication and information about sex education was perceived. As for lifestyles, there are youthful behaviors infused by sociocultural traditions that affect life projects and sexual behavior. Gender relations are precarious, and there are various types of violence that limit effective peacebuilding. Conclusions This study contributes to a priority issue in sexual and reproductive health, with an approach that generates analytical elements to comprehensively expand the social and health interventions required.